2020
DOI: 10.1002/ejp.1655
|View full text |Cite
|
Sign up to set email alerts
|

Perceived validation and criticism in pain: Development of a new measure in chronic pain

Abstract: Background: Research suggests that the way others react to a pain flare-up impacts on psychological and pain-related symptoms in chronic pain (CP). Experiencing validation from others is associated with less negative emotions and better functioning. Contrarily, experiencing criticism is linked to greater pain intensity and worse functioning. Nonetheless, studies are limited by an exclusive focus on spouses rather than significant other relationships, the use of proxy constructs (e.g. social support, responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Pain acceptance implies that an individual continues to pursue life goals and valued activities despite pain, and stops trying to control or avoid pain experiences ( Carriere et al, 2018 ). Feeling validated by others aids acceptance of pain, poses a barrier to internalised stigma, and increases problem-solving behaviour, which in turn can result in better functionality and increased quality of life ( Nicola et al, 2019 ; Penn et al, 2019 ; Andrade Carvalho et al, 2021 ). Our study also indicates that experienced validation can stimulate problem-solving behaviour and acceptance of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain acceptance implies that an individual continues to pursue life goals and valued activities despite pain, and stops trying to control or avoid pain experiences ( Carriere et al, 2018 ). Feeling validated by others aids acceptance of pain, poses a barrier to internalised stigma, and increases problem-solving behaviour, which in turn can result in better functionality and increased quality of life ( Nicola et al, 2019 ; Penn et al, 2019 ; Andrade Carvalho et al, 2021 ). Our study also indicates that experienced validation can stimulate problem-solving behaviour and acceptance of pain.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation might be that a partner’s or friend’s responsiveness and solicitousness (e.g. providing pain medication, helping with chores, asking how they can help) are not necessarily regarded as validation ( Andrade Carvalho et al, 2021 ). An important aspect of active engagement is expressing a shared responsibility in coping with pain and other complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these findings is underscored by repeated observations that patients with FM exhibit greater loneliness, even when compared to patients with other pain disorders, less perceived social support, and increased perceived invalidation from others (Davis et al, 2001;Kool and Geenen, 2012;Kool et al, 2009;Santiago et al, 2017). A study conducted in a chronic pain sample composed mainly of women with FM found that, even when accounting for potential confounders, the perception of others as disregarding, shaming, or judging towards one's pain experience predicted individual pain-related disability (Carvalho et al, 2020). Interpersonal rejectionbe it actual, anticipated, or perceivedand other forms of social disconnection affect pain ratings and pain-and emotion-related neural activity, disrupt pain modulation (Karayannis et al, 2019;Landa et al, 2020;Wolf et al, 2015), and enhance inflammatory activity (Eisenberger et al, 2017).…”
Section: Social Disconnection and Social Painmentioning
confidence: 99%